Dual career in judo. Too good to be true? - Kumric, M.; Marijanovic, T. (The Arts and Sciences of Judo, 2023)
A relatively short career span and an absence of assurances of success in sport has sparked considerable interest in the pursuit of dual career pathways for elite athletes. Unlike benefits of a dual career, which are commonly overstated, the pitfalls, often resulting in dropout in either constituent of the dual career, are largely under-appreciated. As judo has risen to become a very competitive Olympic sport, engaging in dual career pathway in judo can be particu-larly challenging. Therefore, the aim of this qualitative study was to explore contemporary challenges in undergoing dual careers in judo, as viewed from the standpoint of elite judoka from Croatia that successfully follow such a pathway, but also from their respective coaches. Our study showed that even though they encountered many obstacles due to their academic careers, both athletes and their coaches unequivocally confirmed that they would undertake the dual career pathway again. However, since only athletes accomplished in both fields were interviewed, it remains uncertain whether these results translate to a future generation of athletes that considers pursuing dual careers.